Community Service: Strengthening Youth Capacity through Political Literacy in Safeguarding Public Policy in the Peri-Urban Areas of Palangka Raya - Sri Mujiarti Ulfah; Nurul Hikmah; Syamsuri; Yunus Praja Panjika; Suprayitno; Mahmudin Sirait; Ridha Ramadhany; Osi Oskarina Saragih; Cyntia Lupita Sari; Trisni Salsa Ramadina; Ahmad Robi Ul’zikri; Rizki Masyabandi; Muhammad Ruzaini Abdi (PT Polstac Repositori Riset, 2026)
Background: Generation Z, which constitutes 27.94 percent of Indonesia’s population and accounts for 22.85 percent of the Permanent Voter List in the 2024 General Election, represents a significant electoral force with the potential to reshape the national political landscape. However, political understanding among this generation remains largely normative, accompanied by limited critical analytical capacity toward public policy, including an insufficient grasp of the strategic role of organizations in the policy process. Contribution: This Community Service activity aims to strengthen youth capacity by enhancing political literacy to enable them to effectively oversee and engage with public policy, in partnership with the Islamic Student Association at the University of Palangka Raya in Palangka Raya. Method: A survey research method was also used to assess the level of understanding among 25 members of the Islamic Student Association at the University of Palangka Raya. Results: The program proved effective in advancing youth political literacy by requiring a multidimensional approach that integrates cognitive literacy for critical analysis, technical literacy for fact verification, and ethical literacy for responsible political communication